Assessment of maternal drug intake by urinary bio monitoring during pregnancy and postpartally until the third perinatal year. Issue 4 (22nd December 2015) - Hoeke, Henrike; Roeder, Stefan; Bertsche, Thilo; Borte, Michael; von Bergen, Martin; Wissenbach, Dirk K.
Abstract: Purpose: Although sales of prescribed and over‐the‐counter (OTC) medication are rising, little is known about individual drug intake. This study was aimed to obtain complementary information about drug intake. Method: Information on drug utilization was obtained in a female cohort for five different time points (TP): 36th week of pregnancy ( n  = 622), 7th perinatal week ( n  = 533), 3rd perinatal month ( n  = 340), and 1st perinatal ( n  = 534) and 3rd perinatal year ( n  = 324) by a validated urine screening method. Results: Drugs were detected 807 times among all analyzed samples ( n  = 2353) with less drug intake for early TP compared with later TP (~24.4%, n  = 152; ~33.8%, n  = 180; ~23.2%, n  = 79; ~42.5%, n  = 227; and ~52.2%, n  = 169). The diversity of drugs increased from 25 up to 40 different drugs for the investigated period. OTC drugs were detected most frequently reflected by the top three drugs: acetaminophen (~37%, n  = 292), ibuprofen (~23%, n  = 183), and xylometazoline (~12%, n  = 98). Mainly guideline‐orientated drug therapy was observed. However, contraindicated ibuprofen intake during third trimester urine samples ( n  = 26) and a repeated usage of acetaminophen and/or ibuprofen ( n  = 9), as well as xylometazoline ( n  = 7), reveal missing information about drug safety. Conclusion: Bio monitoring was applied for detection of drug intake revealing a lack of information about OTC products and their health risks. Hence, information about health risks for certain drugs and patient groups must be improved for and by pharmacists, to avoid (i) usage of contraindicated drugs and (ii) abuse of OTC drugs. Copyright © 2015 John Wiley & Sons, Ltd.